Evaluation of the Reversal of Multidrug Resistance by Ribonucleic Acid Interference in a Human Colon Cancer Model Using a Luciferase Reporter Gene and Coelenterazine - Yong Hyun Jeon; Seon-ae Bae; Yong Jin Lee; You La Lee; Sang-Woo Lee; Ghil-Suk Yoon; Byeong-Cheol Ahn; Jeoung-Hee Ha; Jaetae Lee (Molecular Imaging)
The reversal effect of multidrug resistance ( MDR1 ) gene expression by adenoviral vector-mediated MDR1 ribonucleic acid interference was assessed in a human colon cancer animal model using bioluminescent imaging with Renilla luciferase (Rluc) gene and coelenterazine, a substrate for Rluc or MDR1 gene expression. A fluorescent microscopic examination demonstrated an increased green fluorescent protein signal in Ad-shMDR1- (recombinant adenovirus that coexpressed MDR1 small hairpin ribonucleic acid [shRNA] and green fluorescent protein) infected HCT-15/Rluc cells in a virus dose-dependent manner. Concurrently, with an increasing administered virus dose (0, 15, 30, 60, and 120 multiplicity of infection), Rluc activity was significantly increased in AdshMDR1-infected HCT-15/Rluc cells in a virus dose-dependent manner. In vivo bioluminescent imaging showed about 7.5-fold higher signal intensity in Ad-shMDR1-infected tumors than in control tumors ( p < .05). Immunohistologic analysis demonstrated marked reduction of P-glycoprotein expression in infected tumor but not in control tumor. In conclusion, the reversal of MDR1 gene expression by MDR1 shRNA was successfully evaluated by bioluminescence imaging with Rluc activity using an in vivo animal model with a multidrug resistance cancer xenograft.